Psychological patterns in pre-graduate students in Tirupati district - Kapu, Ashok Kumar Reddy; Upadrasta, Venkata Prasad; Sibbala, Bharathi; Bathina, Hemalatha; Sadasivuni, Renuka; Ponna, Satyendra Nath; Babu Geddam, J. J. (International Journal Of Community Medicine And Public Health, 2024)
Background: Adolescent age can be a stressful experience for young people with a wide range of concerns. Comprehensive studies on psychological patterns among pre-graduate students in India are meagre. Therefore, this study aimed to assess psychological morbidities and quality of life in them. Methods: The study recruited 567 students aged 15-18 years, who pursued pre-graduate courses at government (300) and private (267) colleges in and around Tirupati and Chandragiri, Andhra Pradesh, India. Information was collected about their physical and psychological health, substance abuse and usage of electronic gadgets. The levels of stress, anxiety, depression, and sleeplessness were assessed. Results: A significant association was observed in the levels of stress, anxiety, and depression among government and private college students at levels of 1%, 10% and 5%, respectively. Higher levels of depression were observed in 44.8% of students; depression was high in girls and government college students. Often, girls experience higher levels of stress leading to psychological illnesses than boys due to their inability to share their feelings and fears among family members. The proportion of poor family health indicators was significantly high in students with moderately low levels of anxiety. Poor sleep had decreased as the depression worsened from borderline to higher levels in boys and decreased even with mild mood disturbances in girls. Conclusions: Management strategies at personal, institutional and social levels are to be developed after understanding the risk factors of psychological morbidities in students.